The innovation of electronic technology devices on jewellery / Muhammad Shafiq Muda - Muda, Muhammad Shafiq (2013)
This research discusses about the potential combinations of electronic technology device and jewellery as the new approach in producing jewellery products. A research study has been made between the two main areas which is jewellery and electronic devices. Jewellery is an expression of the human need to adorn the body and look beautiful. Many jewellery design are available in market for example the necklaces, rings, bracelets, and earring. At the same time there are a variety of electronic devices which could easily attract the consumers especially students and people who is working. An electronic device is a device widely used in helping humans to communicate and do a work. Basically, jewellery adorns the body, and has very limited in term of functionality, through the ages the function of jewelry is more for fashion and body accessories. However, researcher looking to change the way of people thinking about the jewellery we wear. In this study, researcher will discuss the advantages by using jewellery which has a combination with electronic technology devices. As a jewellery maker and designer, researcher will demonstrate a different approach to the development of electronic jewellery. Finally, by using the high technology approach as a part on jewellery, it can give the jewellery a new identity that not only limited for accessories but also features advance technology. It is important for jewellery industries to have something new development for the future in order to make sure that the jewellery industry can compete with other accessories.